IMPLEMENTASI KEBIJAKAN PENEGAKAN HUKUM DI INDONESIA DALAM PERSPEKTIF SOSIOLOGI HUKUM - Raden Selly Indrini Putri (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
Law enforcement is a very essential and substantial aspect in the concept of a state based on law, such as in Indonesia. This is because one of the elements to create or restore balance in the social order is law enforcement. The type of research used in this legal study is normative legal research (doctrinal research). Normative legal research is research based on legal materials (library based) that focuses on reading and studying primary and secondary legal materials. Thus, in legal research conducted to produce new theories, arguments, or concepts as prescriptions to solve the problems faced, the answers are whether they are right, inappropriate, or wrong. This research shows that law is considered effective if it aligns with the regulations established in legislation and meets societal expectations; as a result, the presence of such law can achieve social order within the community.